Metasomatic wolfeite and associated phosphates from the Otov I granitic pegmatite, western Bohemia - Masau,M.; Stanek,J.; Cerny,P.; Chapman,R. (Journal of the Czech Geological Society, 2000)
The pegmatite Otov I, outcropping on Vetrny vrch at the village of Otov, western Bohemia, belongs to the beryl-columbite-phosphate subtype of rare-element granitic pegmatites with rare spodumene. To date, twenty species of phosphates were identified in this pegmatite, and twelve others were recognized during the present study. Wolfeite is established here as a significant metasomatic mineral with average Mn/(Mn+Fe)(at.) of 0.46, F content largely below the detection limit of electron microprobe, α 1.741, β 1.743, γ 1.746, γ - α 0.005, (+)2V medium (calc. 37°), a 12.327(3),b 13.225(3), c 9.845(2) Å, β 108°23', V 1522.95(47) Å3. The primary precursor of wolfeite was (I) arrojadite-dickinsonite studded with sporadic grains of zircon (with inclusions of uraninite) and sphalerite (with droplets of chalcopyrite). Arrojadite-dickinsonite was first veined by (II) a very fine-grained assemblage of muscovite, (Fe, Mn, Al, Ca, Mg, Li)-bearing phosphates (lazulite-scorzalite, eosphorite, samuelsonite?, triphylite, montebrasite) and minor calcite. Subsequent replacement of most of the arrojadite-dickinsonite generated (III) fine-grained wolfeite with interstitial F-bearing hydroxylapatite. Partial replacement of triphylite by alluaudite, hagendorfite and UK-D was coeval with, and spatially preceded, wolfeite metasomatism. Late low-temperature (IV) replacements and veinings permeating the preceding assemblages include ludlamite, goyazite, hydroxylchlorapatite, fairfieldite? and chlorite?. The whole phosphate assemblage is remarkably poor in F, but enriched in Cl in late stages, and it is generally strongly reduced. Substantial contents of Ca, Mg, Sr and Cl, in the virtual absence of Ba, indicate contamination by components of the gabbroic wallrock at both magmatic and late hydrothermal stages.
Keywords: Wolfeite; arrojadite; dickinsonite; lazulite; samuelsonite; triphylite; apatite; alluaudite; goyazite; granitic pegmatite; Bohemia; Czech Republic